Matter of pride ; A mental case ; Regine in season [videorecording] - Lazaro, Cheche (The Probe Team)
A story about the SEA Games preparation for the 1991 hosting of the Philippines. A look at the National Mental Hospital reported fund mess. Regine Velasquez stages a concert at Ultra.